Between fiction and reality: The impact of audiovisual productions on the perception of Forensic Odontology (Research, Society and Development, 2025)
Introduction: Audiovisual productions play a significant role in disseminating scientific knowledge, including in Forensic Odontology. However, films and series, especially police dramas, often portray a distorted forensic reality. Productions such as CSI: Crime Scene Investigation contributed to the emergence of the “CSI Effect,” creating unrealistic expectations regarding the speed, accuracy, and technological resources involved in investigations. This study aims to analyze how these media influence public and academic perceptions of Forensic Odontology and discusses the use of audiovisual content in active methodologies to promote critical learning. Methodology: A narrative literature review was carried out between January and March 2025 using databases such as PubMed, Google Scholar, and BVS to assess how films and series influence perceptions of Forensic Odontology. Only complete and relevant studies on audiovisual media, forensic science, and education were included. The selected works were qualitatively analyzed with emphasis on sociocultural impacts and the educational use of audiovisual resources. Because it was a theoretical review, ethical approval was not necessary. Results and Discussion: Regarding the “CSI Effect,” its impact is evident not only in popular perception but also within legal and educational settings. Nevertheless, the conscious use of these media, combined with active learning methodologies, can transform entertainment into an effective educational tool. Conclusion: It is concluded that although audiovisual productions often distort forensic reality, they can also enhance learning and contribute to the appreciation of Forensic Odontology, as long as they are interpreted through a critical and educational lens.